Global solutions for teams - "Odenwald, Sylvia B." (London, 1996)
Attempting to overcome distance and cultural differences in accomplishing common goals, this guide shows how certain companies have turned their international into a competitive advantage. It looks at how to implement productive cross-functional and cross-location teams; successfully manage the three phases of multinational teaming collision, coexistence and collaboration; and select and lead teams of individuals from diverse cultures in developing productive work systems.
Keywords: Multinationals